Activation of subtilisin Carlsberg in hexane by lyophilization in the presence of fumed silica - Würges, Kerstin; Pfromm, Peter H.; Rezac, Mary E.; Czermak, Peter (My University, 2005)
Subtilisin Carlsberg (SC) was lyophilized from an aqueous buffer solution containing different amounts of unmodified commercial fumed silica. The activity of the enzyme/fumed silica preparation in hexane was compared to pure freeze-dried enzyme, and to a freeze-dried preparation reported in the literature with potassium chloride as additive. A sharp increase in enzyme activity was found to correlate with an increasing amount of fumed silica added to the enzyme solution prior to freeze-drying. A weight-ratio of 98.5wt% fumed silica relative to the mass of the final enzyme/fumed silica preparation led to about 130 fold increased activity of SC in hexane (when compared to pure lyophilized SC in hexane). This is about twice the activation effect compared to including potassium chloride in the buffer solution before freeze-drying [1]. When freezing at -20ºC instead of in liquid nitrogen, even better activation was observed with fumed silica. We hypothesize that the activation of SC in hexane by immobilization of the enzyme on fumed silica is likely due to the distribution of the enzyme on the large surface area of fumed silica. This alleviates mass transfer limitations.
Keywords: Fumed silica; Activation of subtilisin Carlsberg; Immobilization; Hexane; Lyophilization